Pariah politics understanding Western radical islamism and what should be done - Saggar, Shamit (Oxford Univ. Press, 2009)
'Pariah Politics' breaks new ground in examining the issue of western Islamist extremism from the perspective of government. It links underlying causes to the capacity of governments to respond directly and to influence others.